Body shape, adiposity index, and mortality in postmenopausal women: Findings from the Women's Health Initiative. Issue 5 (15th March 2016) - Thomson, Cynthia A.; Garcia, David O.; Wertheim, Betsy C.; Hingle, Melanie D.; Bea, Jennifer W.; Zaslavsky, Oleg; Caire‐Juvera, Graciela; Rohan, Thomas; Vitolins, Mara Z.; Thompson, Patricia A.; Lewis, Cora E.
Abstract : Objective: Studies evaluating the relationship between body mass index (BMI) and mortality demonstrate a U‐shaped association. To expand, this study evaluated the relationship between adiposity indices, a body shape index (ABSI) and body adiposity index (BAI), and mortality in 77, 505 postmenopausal women. Methods: A prospective cohort analysis was conducted in the Women's Health Initiative to ascertain the independent relationships between adiposity indices and mortality in order to inform on the clinical usefulness of alternate measures of mortality risk. ABSI (waist circumference (cm)/[BMI 2/3 × height (cm) 1/2 ]), BAI (hip circumference (cm)/[height (m) 1.5 ] ‐ 18), weight, BMI, and waist circumference (WC) were evaluated in relation to mortality risk using adjusted Cox proportional hazards regression models. Results: ABSI showed a linear association with mortality (HR, 1.37; 95% CI, 1.28‐1.47 for quintile 5 vs. 1) while BMI and BAI had U‐shaped relationships with HR of 1.30; 95% CI, 1.20‐1.40 for obesity II/III BMI and 1.06, 95% CI, 0.99‐1.13 for BAI. Higher WC (HR, 1.21; 95% CI, 1.13‐1.29 for quintile 5 vs. 1) showed relationships similar to BMI. Conclusions: ABSI appears to be a clinically useful measure for estimating mortality risk, perhaps more so than BAI and BMI in postmenopausal women.